Utilization of Digital Libraries as a Learning Resource in Improving the Quality of Student Learning at Public Middle School 2 West Seram - La Alfin Masahu; Titus Gaite; Jumiati Tuharea (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to describe the use of digital libraries as a learning resource in improving the quality of student learning at SMP Negeri 2 Seram Barat. This study uses descriptive qualitative research which aims to find out how the benefits of digital libraries as learning resources in improving the quality of student learning as well as supporting and inhibiting factors in describing the use of digital libraries as learning resources in improving the quality of student learning at SMP Negeri 2 Seram Barat. data collection techniques are used by observation, interviews, documentation studies, the results of this study indicate that there are problems in the use of digital libraries as learning resources in improving the quality of student learning